iid2022: a workshop on statistical methods for event data in astronomy - Feigelson, Eric D.; Bonamente, Massimiliano (Frontiers in Astronomy and Space Sciences, 2023)
We review the iid2022 workshop on statistical methods for X-ray and gamma-ray astronomy and high--energy astrophysics event data in astronomy, held in Guntersville, AL, on Nov. 15-18 2022. New methods for faint source detection, spatial point processes, variability and spectral analysis, and machine learning are discussed. Ideas for future developments of advanced methodology are shared.